How can we take advantage of halophyte properties to cope with heavy metal toxicity in salt-affected areas - Lutts, Stanley; Lefèvre, Isabelle (Annals of botany, 2015)
BACKGROUND: Many areas throughout the world are simultaneously contaminated by high concentrations of soluble salts and by high concentrations of heavy metals that constitute a serious threat to human health. The use of plants to extract or stabilize pollutants is an interesting alternative to classical expensive decontamination procedures. However, suitable plant species still need to be identified for reclamation of substrates presenting a high electrical conductivity. SCOPE: Halophytic plant species are able to cope with several abiotic constraints occurring simultaneously in their natural environment. This review considers their putative interest for remediation of polluted soil in relation to their ability to sequester absorbed toxic ions in trichomes or vacuoles, to perform efficient osmotic adjustment and to limit the deleterious impact of oxidative stress. These physiological adaptations are considered in relation to the impact of salt on heavy metal bioavailabilty in two types of ecosystem: (1) salt marshes and mangroves, and (2) mine tailings in semi-arid areas. CONCLUSIONS: Numerous halophytes exhibit a high level of heavy metal accumulation and external NaCl may directly influence heavy metal speciation and absorption rate. Maintenance of biomass production and plant water status makes some halophytes promising candidates for further management of heavy-metal-polluted areas in both saline and non-saline environments.
Keywords: chlorid sodný; Sodium Chloride; Biodegradation, Environmental; látky znečišťující půdu; Wetlands; Mining; halotolerantní rostliny; Desert Climate; Environmental Restoration and Remediation; pouštní klima; biodegradace; mokřady; Salt-Tolerant Plants; těžké kovy; hornictví; Metals, Heavy; regenerace a remediace životního prostředí; Soil Pollutants